Cover Feature: Water Formation in Non‐Hydrolytic Sol–Gel Routes: Selective Synthesis of Tetragonal and Monoclinic Mesoporous Zirconia as a Case Study (Chem. Eur. J. 8/2021). Issue 8 (7th December 2020) - Wang, Yanhui; Bouchneb, Maroua; Mighri, Rimeh; Alauzun, Johan G.; Mutin, P. Hubert
Abstract : Water in non‐hydrolytic sol‐gel : In situ water formation during the synthesis of mesoporous zirconia has been systematically investigated. Significant amounts of water were found in several cases, notably in the reactions of Zr(O n Pr)4 with ketones and of ZrCl4 with alcohols or acetone. Conversely, the reactions of Zr(O n Pr)4 with acetic anhydride or benzyl alcohol at moderate temperature (200 °C) and of ZrCl4 with diisopropyl ether were strictly non‐hydrolytic. Water played a major role on the structure of the final zirconia: tetragonal ZrO2 was favored in strictly non‐hydrolytic routes, while monoclinic ZrO2 was favored in the presence of water. More information can be found in the Full Paper by P. H. Mutin et al. on page 2670 .